Implementasi Program Penyuluhan Pengelolaan Sampah Untuk Menumbuhkan Kepedulian Lingkungan Pada Siswa Sd Negeri 100 Seluma - Ariel Darma Yendi; Marisa Marisa; Amanda Triana Agustina; Sela Dwi Kurnia; Anjela Delaini (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Waste management remains one of the major environmental challenges, including within school environments. Low awareness among elementary school students regarding environmental cleanliness may lead to poor waste disposal behavior. Therefore, environmental education from an early age is essential through educational outreach programs involving university students participating in Community Service Programs (Kuliah Kerja Nyata/KKN). This article aims to describe the implementation of a waste management education program designed to foster environmental awareness among students of SD Negeri 100 Seluma. The program was conducted by KKN students from the University of Bengkulu, Group 97, Period 108, using interactive lectures, waste-sorting demonstrations, discussions, and question-and-answer sessions. The results indicate that students actively participated throughout the activities. They demonstrated improved understanding of organic and inorganic waste, recognized the environmental impacts of improper waste disposal, and developed greater awareness of maintaining school cleanliness. The outreach program successfully encouraged environmentally responsible behavior and strengthened students' awareness of sustainable waste management practices.